PHONOLOGY OF KAUR LANGUAGE IN GENERATIVE THEORY - Hadi, Wisman; Pastika, I Wayan; Suparwa, I Nyoman; Putra, A.A. Putu (e-Journal of Linguistics, 2012)
Kaur language (abbreviated to KL) is one of the varieties of Central Malay, which is spoken by the people living in Kaur Regency, Bengkulu Province. This study focuses on three problems; they are (1) how the segments of sounds in KL were represented and what features distinguished them; (2) how the syllabic structures, phonetic symbols, and the patterns of stress in KL were represented; and (3) how and why the phonological processes in KL took place; and what its phonological rules were like? The general objective of this study was to analyze the phonological system of Kaur language, and the specific objective was to explain the sound segments, syllabic structure, phonotactic system, and phonological processes and rules of KL using the Generative Theory. Descriptive-qualitative approach was used in this study. The data were collected using interview and documentation methods and were analyzed and presented formally and informally. The results of the study showed that there were 23 phonological processes in Kaur language represented by /a, ?, i, u, p, b, t, d, c, ?, k, g, ?, m, n, ?, ?, s, ?, h, l, w, j/. These segments were  phonetically realized by [a, ?, ?, ?, i, ?, e, ?, u, ?, o, ?, a), ?), ?), ?), i), ?), e), ?), u), ?), o), ?), p, p > , b, b > , t, t > , d, c, ?, k, k > , g, g > , ?, m, n, ?, ?, s, z, Ä, ?, h, h), l, w, j, w , j ]. Every segment was described by using 17 distinctive features, which were [syllabic, son., cons., cont., nas., lat., ant., cor., gut., plosives stops, voiced, high, front, back, low, ATR, round.]. In addition, it was found that there were 3 diphthongs, 9 series of vowels, 14 clusters of consonants, 22 series of consonants, and several unique series of vowel-consonants, 36 syllabic structures of bases, 5 basic patterns of syllabic structures of affixes, and 4 structures of mixed affixes. The phonological processes are described in 49 phonological rules. Of these 49 rules, there are several ordered phonological rules.
Keywords: Kaur language, syllable structure, phonological processes